Pengaruh Tingkat Pendidikan, Pendapatan dan Pengetahuan Produk Terhadap Minat Menjadi Nasabah Di PT Takaful Keluarga Serang - Khusnul Khatimah; Suryani Suryani; Ikin Ainul Yakin (Studia Economica : Jurnal Ekonomi Islam, 2026)
The purpose of this study is to identify the influence of education level, income, and product knowledge on the interest in becoming a customer at PT Takaful Keluarga Serang Branch. This study is a study that applies quantitative methods, uses primary data as a source of information, and relies on questionnaires for data collection. The sample selection was carried out by purposive sampling, for the number of samples in this study taking 90 respondents who were used as research samples based on the results of the calculation of the Slovin formula used. Data analysis techniques used include classical assumption tests, multiple linear regression tests, and hypothesis testing. The findings from partial hypothesis testing indicate that the variable of education level influences the interest in becoming a customer at PT Takaful Keluarga Serang Branch, as shown by the calculated t value of 3.155> t table 1.666 with a significance level of 0.002 <0.05. Income influences the interest in becoming a customer at PT Takaful Keluarga Serang Branch, as shown by the calculated t value of 3.020> t table 1.666 with a significance level of 0.003 <0.05. Product knowledge influences the interest in becoming a customer at PT Takaful Keluarga Serang Branch, as shown by the calculated t value of 2.562 > t table 1.666 with a significance level of 0.012 < 0.05